Alih Teknologi Budidaya Jamur Coprinus comatus Menggunakan Jerami Padi pada Karang Taruna Desa Sambiroto Kabupaten Demak - Murrinie, Endang Dewi; Yuliani, Farida; Ariyanto, Shodiq Eko (Politeknik Negeri Jember, 2024)
Rice harvested waste in the form of straw in Sambiroto Village, Demak Regency, is currently not widely used, so that straw is only burned on land which causes air pollution and destroys beneficial soil microorganisms. Rice straw can be used as a growing medium for chicken thigh mushrooms (Coprinus comatus), but people do not know and know how to cultivate and post-harvest process and market these chicken thigh mushrooms. Chicken Thigh Mushroom is one type of mushroom consumption that has quite the potential to be cultivated in Indonesia because it has a high nutritional content and contains several compounds that are efficacious for health or as medicinal ingredients. Therefore, community service was carried out regarding the introduction of chicken thigh mushroom cultivation technology using straw media, post-harvest processing, and marketing. The target audience is the Village Community, in this case, the Youth Organization of Sambiroto Village, Demak Regency.